2008
DOI: 10.1016/s1472-6483(10)60476-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of short and long GnRH agonist protocols using recombinant gonadotrophins for IVF/ICSI treatments

Abstract: This is a prospective comparative study investigating cost and effectiveness of IVF/ intracytoplasmic sperm injection (ICSI) treatments after stimulation with recombinant gonadotrophins following either the short or long gonadotrophin-releasing hormone (GnRH) agonist protocol. Patients in the short protocol (n = 120) were administered buserelin nasal sprays from day 2 of the menstrual cycle and recombinant FSH from day 5. Patients in the long protocol (n = 120) were administered buserelin from the previous mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[8,9]. Other cost-effectiveness analyses have found that the cost of COH and IVF outcomes also depend on the clinical choice of medicines and GnRHagonist/GnRH-antagonist for ovarian stimulation and the duration of stimulation [10][11][12][13][14][15][16][17]. For evaluation of the protocols in many of these studies, the clinical end-point of interest is the number of live-born children.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9]. Other cost-effectiveness analyses have found that the cost of COH and IVF outcomes also depend on the clinical choice of medicines and GnRHagonist/GnRH-antagonist for ovarian stimulation and the duration of stimulation [10][11][12][13][14][15][16][17]. For evaluation of the protocols in many of these studies, the clinical end-point of interest is the number of live-born children.…”
Section: Introductionmentioning
confidence: 99%
“…Although follicular growth can be induced by FSH in the total absence of LH, the resulting follicles have developmental deficiencies such as abnormally low production of E2 and an inability to luteinize and rupture in response to hCG stimulus [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…LH flare-up during the short protocol does not seem to impair the treatment outcome using recombinant gonadotrophins. The short GnRH agonist protocol is an effective and cheaper choice for IVF/ICSI treatments [12].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies (Frydman et al, 1988a(Frydman et al, , 1988bHo et al, 2008) showed no difference in delivery rate between short and long GnRH agonist protocols.…”
Section: Introductionmentioning
confidence: 88%